Agreement of anterior segment measurements between four diagnostic imaging devices in myopic patients. (2nd December 2021) - Placide, John; Neves Da Silva, Helio V.; McCabe, Shannon E.; Ronquillo, Yasmyne C.; Moshirfar, Majid
ABSTRACT: Purpose: To compare the inter-device agreement of anterior chamber depth (ACD), central corneal thickness (CCT), flat keratometry (K1), steep keratometry (K2), corneal astigmatism (ΔK), and white-to-white (WTW) measurements. Methods: This is a retrospective study with 73 myopic patients (142 eyes). We extracted and compared anterior segment measurements (ACD, CCT, K1, K2, ΔK, and WTW) of four devices (OPD-Scan III, Pentacam HR, Lenstar LS 900, and Galilei G4), and performed pairwise agreement comparisons between them. Results: Agreement analyses revealed that the most agreement occurred: in Pentacam HR and Galilei G4 for ACD measurements, in Pentacam HR and Lenstar LS 900 for CCT measurements, in OPD-Scan III and Galilei G4 for WTW measurements, in OPD-Scan III and Pentacam HR for K1 and K2 measurements, and OPD-Scan III and Galilei G4 for ΔK measurements. Conclusion: OPD-Scan III is interchangeable with both Galilei G4 and Lenstar LS 900 for WTW measurements. OPD-Scan III and the Pentacam-HR are interchangeable in K1, K2, and ΔK measurements. OPD-Scan III and Lenstar LS 900, and OPD-Scan III and Galilei G4 are interchangeable in K1 and ΔK measurements, respectively.